Continuous finite‐time control of four‐leg inverter through fast terminal sliding mode control. (23rd February 2020) - Pichan, Mohammad; Arab Markadeh, Gholamreza; Blaabjerg, Frede
Summary: A favorable option to supply unbalanced loads and provide the neutral wire is the four‐leg inverter. Controllers with high robustness and dynamic response should be used to adjust the inverter load voltages for unknown, unbalanced, and nonlinear loads. Sliding mode controls (SMCs) have a simple structure, good robustness against model parameter uncertainties, and desirable transient response. However, chattering phenomena, variable switching frequency, and error convergence to the operating point on infinite time are the main weaknesses of the conventional SMC method. In this paper, to restrict the conversion time to a finite and controllable value, terminal sliding mode control (TSMC) and fast terminal sliding mode control (FTSMC) procedures are proposed to regulate the load voltages of the four‐leg inverter. In these methods, a continuous control output is suggested to fix the switching frequency and reduce chattering phenomena significantly. Furthermore, the proposed methods are highly robust against model parameter uncertainties. Different simulation and experimental results on a 3‐kW test bench under different loading conditions are done to validate the significant performance of the proposed methods.